2009
DOI: 10.1007/s00380-008-1069-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of myocardial performance index obtained either by conventional echocardiography or tissue Doppler echocardiography in healthy subjects and patients with heart failure

Abstract: This study was planned to investigate the normal reference values of myocardial performance index (MPI) obtained by tissue Doppler echocardiography (TDE) and the agreement between MPI measured by TDE and conventional MPI measured by pulsed-wave Doppler (PWD) in healthy subjects and patients with heart failure (HF). Two hundred and three patients with HF and 190 healthy subjects were enrolled in this study. Isovolumic contraction and relaxation time (ICT and IRT) and ejection time (ET) were measured from mitral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…22 In identifying patients with moderately or severely decreased LVEF, MPI had higher specificity, sensitivity, negative predictive value, and diagnostic accuracy. 18 Our data seem therefore to confirm previous results by Vizzardi et al, 23 who demonstrated in outpatients setting as MPI is independently related to the incidence of cardiovascular hospitalizations.…”
Section: Discussionsupporting
confidence: 92%
“…22 In identifying patients with moderately or severely decreased LVEF, MPI had higher specificity, sensitivity, negative predictive value, and diagnostic accuracy. 18 Our data seem therefore to confirm previous results by Vizzardi et al, 23 who demonstrated in outpatients setting as MPI is independently related to the incidence of cardiovascular hospitalizations.…”
Section: Discussionsupporting
confidence: 92%
“…15 The components used to calculate the MPI by pulsed-wave Doppler method are sometimes ob- Table I. tained sequentially from different heart beats if mitral inflow and LV ejection signals cannot be clearly recorded simultaneously and its application may be limited by heart rate fluctuation. Further prospective studies are needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…MPI can be derived both from Doppler flow and from TDI measurements [15] where the former is the original version used by Tei et al [16]. Compared to pulsed-wave Doppler used by Tei et al MPI derived from tissue Doppler has been shown to correlate better with LV ejection fraction and functional capacity [17]. Since MPI is an estimate of systolic as well as diastolic ventricular function it has been shown to be a sensitive marker for ventricular function [7].…”
Section: Discussionmentioning
confidence: 99%